Kompetensi Anggota Polri Dalam Penerapan ETLE Guna Pencegahan Distracted Driving Untuk Mewujudkan KAMSELTIBCARLANTAS: Studi Kasus Polda Kalimantan Barat - Imas Niken Kusumaningrum; Ilham Prisgunanto (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
Traffic violations, especially in the 4.0 era, is a new challenge for the Police. The author aims to analyze how the competence of members in implementing ETLE to prevent distracted driving at the West Kalimantan Regional Police to realize Kamseltibcarlantas. In this study using data collection techniques by interview, observation and document study. Data analysis techniques used in qualitative research include interview transcripts, data reduction, analysis, data interpretation and triangulation. Application of ETLE in the Legal Area of the West Kalimantan Regional Police. ETLE is the police's effort to welcome the police 4.0 era. In its implementation, ETLE in West Kalimantan was able to detect traffic violations including traffic light violations, road marking violations, not wearing a safety belt, using a cell phone when driving, going against the flow and not wearing a helmet. The application of ETLE in the jurisdiction of the West Kalimantan Regional Police aims to prevent traffic accidents and create Kamtibselcarlantas. However, the ETLE CCTV cameras in West Kalimantan that have been implemented have not been able to detect vehicle speed where speed can increase the risk of traffic accident fatalities. The human resource capability of the West Kalimantan Regional Police's knowledge and skills-oriented Gakkum Ditlantas Sub-Directorate will be very influential in determining the success of ETLE implementation.